The Students' Motivation In Online English Learning In New Normal Era - Nur Ransyah Hamdani; Sukardi Weda; Rampeng Rampeng (Postgraduate Bosowa University, 2023)
The purpose of this study was (1) to find out the level of the students’ motivation in online English learning in New Normal Era. (2) To analysis the factors that influence the students’ motivation in online English learning in New Normal Era. (3) To find out whether or not the implementation of English online learning fulfills the principle of effective teaching and learning. The research was designed by Mixed Method. The students of Class XI TESHA Department of SMK Negeri 3 Makassar were chosen by the researcher as sample which consists of 30 students. In collecting data, the researcher used interview and questionnaire. From the result it can be show that most of the students has moderate degree motivation in joining English Online learning in New Normal Era. Second, there are three factors that influence the students’ motivation in English online learning, they are learning ability, learning tools and facility and students’ goals. Third, most of the students was interested to implementation of English online learning.